ON THE INFLUENCE OF MEDIA INFORMATION ON READING CULTURE (Universal International Scientific Journal, 2026)
This article studies the impact of media information on reading culture in the contextof a developing digital society. It analyzes changes in reading practice, the features of text perceptionin the media environment, and the changing role of books and reading in the system of cultural values.Both destructive and constructive aspects of the impact of media information on reading culture arestudied. The need to develop media literacy and form a stable motivation for meaningful reading isjustified.
Keywords: reading culture; media information; digitization